Capillary Prolactin and Seizure Diagnosis - J Gordon Millichap (Pediatric Neurology Briefs Publishers, 1991)
The validity of prolactin measurements using capillary blood in the diagnosis of epilepsy was tested in the Departments of Neurology, Neurosurgery, and Pathology, The Johns Hopkins University School of Medicine, Baltimore, MD.